Long-term follow-up of applying autologous bone grafts for reconstructing tympanomastoid defects in functional cholesteatoma surgery - Wei-Che Lan (PeerJ Inc., 2021)
Objectives This study investigated the long-term surgical outcomes of functional cholesteatoma surgery with canal wall reconstruction using autologous bone grafts as the primary material in patients with acquired cholesteatoma. Subjects and Methods Medical charts were retrospectively reviewed for all patients admitted to one institution for surgical intervention between 2010 and 2018. We analyzed 66 patients (66 ears) who underwent functional tympanomastoidectomy involving the use of autologous bone grafts for canal wall defect reconstruction. Surgical outcomes were evaluated by comparing preoperative audiometric results with follow-up data (at least 36 months after surgery). Logistic regression analyses were performed to determine prognostic factors related to long-term hearing success. These factors included classification and stage of cholesteatoma, stapes condition, ossicular chain damage, active infection of the middle ear, state of the contralateral ear, preoperative hearing thresholds, gender, and age. Results The mean follow-up period was 49.2 months. The recidivism rate was 6% (four of 66 ears). The pure-tone average significantly improved from 50.78 ± 19.98 to 40.81 ± 21.22 dB hearing level (HL; p < 0.001). Air–bone gaps significantly improved from 26.26 ± 10.53 to 17.58 ± 8.21 dB HL (p < 0.001). In multivariate logistic regression analysis, early-stage disease (p = 0.021) and pars flaccida cholesteatoma (p = 0.036) exhibited statistically significant correlations with successful hearing preservation. Conclusion Functional cholesteatoma surgery with autologous bone grafts reconstruction is an effective approach to significantly improve hearing with low recidivism rates. Localized disease and pars flaccida cholesteatoma were two independent predictors of successful hearing preservation.